Assessment of the relative benefits of monotherapy and combination therapy approaches to the treatment of hospital-acquired Stenotrophomonas maltophilia pneumonia: a multicenter, observational, real-world study - Liang Chen; Jie Hua; Shujie Hong; Chenyang Yuan; Ruochen Jing; Xuanyu Luo; Yihong Zhu; Le Le; Ziqi Wang; Xiaoli Sun; Xiaopu He (Annals of Intensive Care, 2023)
Abstract Purpose Stenotrophomonas maltophilia is a Gram-negative pathogen that most commonly causes hospital-acquired infections that can be extremely challenging to treat, contributing to underrecognized mortality throughout the world. The relative benefits of monotherapy as compared to combination therapy in patients diagnosed with S. maltophilia pneumonia, however, have yet to be established. Methods Data from 307 patients diagnosed with S. maltophilia hospital-acquired pneumonia (HAP) across four Chinese teaching hospitals from 2016 to 2022 were retrospectively analyzed. Results Of the analyzed patients, 55.7% (171/307) were administered combination definitive therapy, with a 30-day all-cause mortality rate of 41.0% (126/307). A propensity score weighting analysis revealed that compared with monotherapy, combination definitive therapy was associated with a comparable 30-day mortality risk in the overall patient cohort (OR 1.124, 95% CI 0.707–1.786, P = 0.622), immunocompetent patients (OR 1.349, 95% CI 0.712–2.554, P = 0.359), and patients with APACHE II scores < 15 (OR 2.357, 95% CI 0.820–6.677, P = 0.111), whereas it was associated with a decreased risk of death in immunocompromised patients (OR 0.404, 95% CI .170–0.962, P = 0.041) and individuals with APACHE II scores ≥ 15 (OR 0.494, 95% CI 0.256–0.951, P = 0.035). Conclusion The present data suggest that when treating S. maltophilia-HAP, immunocompromised patients and individuals with APACHE II scores ≥ 15 may potentially benefit from combination therapy.